Microelements (As, Cd, Pb, Fe, Cu, Zn, Se, Hg) in commercial crustaceans in the Japan Sea - Irina S. Narevich; Lidia T. Kovekovdova (Известия ТИНРО)
Concentrations of As, Cd, Pb, Hg, Se, Fe, Cu, and Zn in tissues of the commercial crabs and shrimps Chionoecetes opilio, Paralithodes camtschaticus, Pandalus borealis, Pandalus hypsinotus , and Sclerocrangon salebrosa from Primorye waters are determined. The samples were collected by research vessels of Pacific Fish. Res. Center (TINRO) in 2012-2016. Content of metals and arsenic in the soft tissues (from claws and phalanxes of crabs and abdomen of shrimps) was determined by atomic absorption analysis (fiery and flameless methods), using Shimadzu AA-6800 spectrophotometer and mercury analyzer DMA-80 Milestone. As, Cd and Pb concentrations were measured by electrothermal method, with graphite cuvette as an atomizer; Fe, Cu and Zn concentrations were measured in the acetylene/air flame, with single-slot burner as an atomizer and background correction by a deuterium lamp. The standard solutions of the metals were used for calibration. Generally, the microelement composition in soft tissues of all shrimp and crab species is similar. For all species, concentrations of the elements in the soft tissues decrease in the order: Zn > Fe > As > Cu > Se > Cd ~ Pb ~ Hg. All samples are distinguished by heightened concentration of Cu. The following ranges of the toxic metals concentration are observed (mg per kg of wet weight): Pandalus borealis As - 1.6-8.5; Cd - 0.03-0.15; Pb - 0.01-0.02; Pandalus hipsinotus As - 2.78-14.6; Cd - 0.01-0.13; Pb - 0.00-0.01; Sclerocrangon salebrosa As - 5.4-17.3; Cd - 0.01-0.04; Pb - 0.01-0.03; Chionoecetes opilio As - 9.4-14.0; Cd - 0.01-0.05; Pb - 0.01-0.05; Paralithodes camtschaticus As - 3.0-8.8; Cd - 0.0008-0.10; Pb - 0.001-0.009. Cases of exceeding the maximum permissible level of As are detected for all species: in 68.0 % of samples for Paralithodes camtschaticus , in 35.0 % of samples for Sclerocrangon salebrosa , in 33.3 % of samples for Panadalus hipsinotus , in 17.5 % of samples for Panadalis borealis , and in 17.0 % of samples for Chionoecetes opilio .